2019
DOI: 10.1038/s41594-019-0268-0
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the full-length Clostridium difficile toxin B

Abstract: Clostridium difficile is an opportunistic pathogen that establishes in the colon when the gut microbiota is disrupted by antibiotics or disease. C. difficile infection (CDI) is largely caused by two virulence factors TcdA and TcdB. Here, we report a 3.87 Å resolution crystal structure of TcdB holotoxin that captures a unique conformation of TcdB at endosomal pH. Complementary biophysical studies suggest that the CROPs domain of TcdB is dynamic and can sample open and closed co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
121
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(146 citation statements)
references
References 78 publications
(120 reference statements)
16
121
0
Order By: Relevance
“…Initial analysis of the dataset revealed that approximately 50% of the SEMA6A dimers were bound to TcsL using this sample preparation approach. Consequently, 2D and 3D classification resulted in two homogenous datasets corresponding to the TcsL- Figure 3 The architecture of TcsL is similar to previously-determined structures of other clostridial toxins (8,(22)(23)(24) of SEMA6A, which is buried in a TcsL hydrophobic pocket formed by C1433, I1434, Y1471, A1486 and I1493. Indeed, expression of a SEMA6A M109D in SEMA6A knockout cells does not make the cells more sensitive to TcsL, in contrast to wild-type SEMA6A (Fig.…”
supporting
confidence: 65%
“…Initial analysis of the dataset revealed that approximately 50% of the SEMA6A dimers were bound to TcsL using this sample preparation approach. Consequently, 2D and 3D classification resulted in two homogenous datasets corresponding to the TcsL- Figure 3 The architecture of TcsL is similar to previously-determined structures of other clostridial toxins (8,(22)(23)(24) of SEMA6A, which is buried in a TcsL hydrophobic pocket formed by C1433, I1434, Y1471, A1486 and I1493. Indeed, expression of a SEMA6A M109D in SEMA6A knockout cells does not make the cells more sensitive to TcsL, in contrast to wild-type SEMA6A (Fig.…”
supporting
confidence: 65%
“…binding 55 , and E3 binding 54 were then analyzed in terms of their variation across subtypes. E3 binding residues were identified by analysis of PDB structure 6OQ5 54…”
Section: Sequence Clustering and Analysismentioning
confidence: 99%
“…FZD and bezlotoxumab variants also co-occur with each other. (b) Evolutionary conservation mapped to the protein structure of full length TcdB based on PDB 6OQ554 . Eight highly conserved surface patches are indicated, and additional details are inFig.…”
mentioning
confidence: 99%
“…These are two large proteins that contain a common multi-modular domain structure described as the ABCD model (A: biological activity; B: binding; C: cutting; D: delivery) [14]. The crystal structure of toxin A and toxin B has recently been elucidated and reported [15,16]. The toxins are encoded by the tcdA and tcdB genes, respectively, located within a region known as the pathogenicity locus or PaLoc, a chromosomally integrated DNA sequence.…”
Section: Pathophysiology Of CDImentioning
confidence: 99%